TRANSLANGUAGING PRACTICES IN A TERTIARY EFL CONTEXT IN INDONESIA - Emilia, Emi; Hamied, Fuad Abdul (TEFLIN Journal, 2022)
This paper presents partial results of an ethnographic study in 2021, aiming to identify translanguaging (TL) practices (the use of Indonesian and English), their functions and benefits, and the participants’ opinions about such practices in a tertiary English as a foreign language (EFL) context in Indonesia. The study involved 75 participants in four courses organized online (due to the COVID-19 pandemic), in the English Education Study Program of a state university in Bandung, West Java, Indonesia. The study drew on the notion of TL, synthesized with principles of effective online teaching. The data were obtained from a phase of teaching with teachers as researchers in 7 meetings (out of 16 meetings required), informal interviews with the participants after the class, and a questionnaire administered online, involving 46 volunteers. The results reveal that TL practices occurred in all courses, which served different functions, including interpretive, managerial, and interactive functions. The practices benefited the students cognitively, socially, and psychologically. Questionnaire and interview data support observation data and previous research about the use of mother tongue in Indonesian EFL classrooms (Emilia, 2010, 2011) that the majority of students (82.6%) wanted mixed Indonesian and English despite few students’ tendency to use English only in the classroom.